PERAMALAN JUMLAH PRODUKSI TANDAN BUAH SEGAR (TBS) KELAPA SAWIT MENGGUNAKAN METODE FUZZY TIME SERIES (STUDI KASUS: PT KALIMANTAN SAWIT KUSUMA) - Rizka Indriyani Pratiwi; Nur Salam; Maisarah Maisarah (Mathematics Study Program, Faculty of Mathematics and Natural Sciences, Lambung Mangkurat, 2023)
Palm oil is a type of plantation crop that occupies an important position in the agricultural and plantation sectors. This is because oil palm is the largest producer of economic value per hectare in the world. The oil produced by palm oil comes from Fresh Fruit Bunches (FFB) which consist of various levels of maturity. PT Kalimantan Sawit Kusuma is experiencing instability in the amount of production, so forecasting is needed to estimate how to keep the amount of production stable. The method used is fuzzy time series (FTS), which is data forecasting that applies fuzzy sets as a basis for forecasting modeling by processing past data patterns to be applied in predicting future data. The goal is to obtain forecasting results for FFB production from April 2023 to December 2023 and obtain a Mean Absolute Percentage Error (MAPE) value. Forecasting results of Palm Oil FFB Production applying FTS Lee Order 1 in April 2023 to December 2023 are 8,412, 8,309, 8,309, 8,309, 8,309, 8,309, 8,309, 8,309 and 8,309 tons with a MAPE value of 9.07046%. While the forecasting results for Palm Oil FFB Production using FTS Lee Order 2 for April 2023 to December 2023 are 7,309, 8,559, 7,309, 8,559, 7,309, 7,309, 8,559 and 7,309 tons with a MAPE value of 4.80541%.